Dampak Keamanan Data terhadap Kepercayaan dan Loyalitas Pengguna Bank Digital - Samosir, Masda; Cep Adiwihardja; Mochamad Nandi Susila (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The development of information technology has led to the emergence of digital banking applications that are increasingly popular among the public. However, data security and user trust are important issues that need to be studied. This study aims to analyze the influence of data security and user trust on digital banking applications. The method used in this study is the Technology Acceptance Model (TAM) and uses a quantitative approach through the distribution of online questionnaires to obtain data from respondents, which is then processed using SPSS 31 software. The sample for this study consisted of 100 respondents. The results of the multiple linear regression analysis involved three independent variables: data security, ease of use, and user satisfaction. The analysis results show that there is a positive influence between the independent and dependent variables. In addition, the regression coefficient for the data security variable is 38.4%, user convenience is 7.2%, and user satisfaction is 17%. These findings indicate that data security and user satisfaction have a significant influence on the use of digital banking applications, while user convenience has a smaller influence.